Protective effect of 2-aminoethyl diphenylborinate in rat colitis model induced by acetic acid - Aksit, Dilek; Aksit, Hasan; Yildiz, Onur; Dogru, Mustafa Selim; Yay, Arzu Hanim; Baykalir, Burcu Gul; Atessahin, Ahmet (E-Century Publishing Corp, 2016)
Some of the diseases like ulcerative colitis, Crohn disease and certain types of intestinal cancers are not treatable effectively. Our aim was to investigate the protective effects of 2-aminoethyl diphenylborinate (2-APB) on the rats with acetic acid induced colitis. Twenty four Sprague-Dawley rats were randomly divided into the following four groups: (1) control group, (2) colitis group, (3) 2-APB group, (4) colitis+2-APB group. Twenty four hour after the acetic acid administration blood samples were collected under the ether anesthesia. After the collection of all blood samples rats were euthanized by cervical dislocation under the anesthesia and abdomen was opened and the colon was taken. Superoxide dismutase activities, total antioxidant capacity, malondialdehyde, ceruloplasmin, total cialic acid and iron (Fe2+) levels were measured using blood samples. Superoxide dismutase activities, total antioxidant status, malondialdehyde and DNA fragmentation levels were evaluated at colon tissues. Paraffin sections of colon tissue were subjected to: a) immunohistochemistry (Bcl-2), b) TUNEL-staining (apoptotic cells), c) histopathological (masson's trichrome staining) examinations. Sections were evaluated semiquantitatively. Induction of colitis caused pathological and biochemical alterations in rat colon. Rates of apoptosis increased concomitantly with the levels of oxidants in colitis group, while activities of antioxidant enzymes decreased remarkably. Administration of 2-APB however, ameliorated the biochemical and pathological alterations in rats caused by colitis. In the light of the data obtained from the present study it could be recommended that using of 2-APB in colitis could be considered as a remedy at least as a complementary drug.
Keywords: Apoptosis; 2-aminoethyl diphenylborinate; colitis